Reducing Your Risk for Cancer: The Power of Food - Jodi Fitzgerald; Danielle Nelson; Madison Woodard; Jeanette Andrade (EDIS)
Cancer is the #2 cause of death within the United States, where 2 out of every 5 people will be diagnosed with some form of cancer within their lifetime. Forty-five percent of cancer deaths may have been caused by risk that factors that you can change, such as weight, diet, and lifestyle. This new 6-page publication describes the modifiable risk factors for cancer and tips to reduce your risk for cancer. Written by Jodi Fitzgerald, Danielle Nelson, Madison Woodard, and Jeanette Andrade, and published by the UF/IFAS Food Science and Human Nutrition Department.